2017
DOI: 10.1038/mi.2016.121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of depot-medroxyprogesterone acetate on the immune microenvironment of the human cervix and endometrium: implications for HIV susceptibility

Abstract: Depot-medroxyprogesterone acetate is a commonly used injectable contraceptive that has been associated with an increased risk of HIV acquisition. This study compares effects of depot-medroxyprogesterone acetate on immune parameters from several reproductive tract compartments relevant to HIV-1 susceptibility in upper reproductive tract samples from 15 depot-medroxyprogesterone acetate users and 27 women not on hormonal contraceptives. Compared to samples from unexposed women in the mid-luteal phase, depot-medr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…Interestingly, a recent transcriptomic study revealed that women using the progestin‐based hormonal contraceptives DMPA or levonorgestrel intrauterine system (LNG‐IUS) have increased expression of genes involved in chemotaxis, attachment, and inflammation from whole tissue samples from the endometrium . It was also determined that women treated with DMPA have higher numbers of endometrial macrophages which have been shown to be the primary target for HIV‐1 infection in the endometrium . Thus, our study and others suggest that DMPA influences the numbers of HIV‐1 target cells through chemotactic recruitment.…”
Section: Discussionmentioning
confidence: 48%
“…Interestingly, a recent transcriptomic study revealed that women using the progestin‐based hormonal contraceptives DMPA or levonorgestrel intrauterine system (LNG‐IUS) have increased expression of genes involved in chemotaxis, attachment, and inflammation from whole tissue samples from the endometrium . It was also determined that women treated with DMPA have higher numbers of endometrial macrophages which have been shown to be the primary target for HIV‐1 infection in the endometrium . Thus, our study and others suggest that DMPA influences the numbers of HIV‐1 target cells through chemotactic recruitment.…”
Section: Discussionmentioning
confidence: 48%
“…[3][4][5][6][7] An ongoing randomized study called the ECHO (Evidence for In our prior study, we showed that altered expression of putative HIV/SIV factors during the luteal phase of the menstrual cycle could contribute to greater risk of vaginal acquisition during this phase. [3][4][5][6][7] An ongoing randomized study called the ECHO (Evidence for In our prior study, we showed that altered expression of putative HIV/SIV factors during the luteal phase of the menstrual cycle could contribute to greater risk of vaginal acquisition during this phase.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have expressed more concern with use of DMPA than with LNG-based contraception with respect to HIV acquisition risk. [3][4][5][6][7] An ongoing randomized study called the ECHO (Evidence for IL-10, a multifunctional cytokine with both proinflammatory and immunoregulatory properties, is known to block viral clearance and enhance HIV pathogenesis. 24 Previous reports have demonstrated that viruses specifically exploit IL-10 to evade the host immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depo-Provera users have higher levels of activated endometrial T cells along with a higher percentage of endometrial CD4 + naïve and CM subsets compared to women not using hormonal contraceptives, although there is no difference in their TEM subsets (47). We observed a similar increasing tread of naïve and CM CD4 + T cells subsets in response to Depo-Provera, especially in black patients, indicating changes in CD4 + T cell subsets by Depo-Provera may not be compartmentalized.…”
Section: Discussionmentioning
confidence: 99%